(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In this article, the results of the research aimed at determining the level of development of critical thinking skills of future teachers in the process of training pedagogical personnel in higher educational institutions as a decisive requirement for solving pedagogical problems are widely covered.